Analisis Manajemen Pembiayaan Pendidikan Dalam Menunjang Proses Pendidikan di Perguruan Tamansiswa Cabang Pematangsiantar - Arif Syukri Nasution (Forum Kerjasama Pendidikan Tinggi, 2022)
The research objectives are: 1. To find out budget planning, expenditure income, use of financing and supervision of financing at the Tamansiswa Pematangsiantar Branch. 2. To find out the financing of education in supporting the learning process at the Tamansiswa College Pematangsiantar Branch. The results of this study can be concluded, namely: 1. The preparation of an income budget plan at the Tamansiswa Pematangsiantar Branch consists of 2, namely a budget plan whose funding source comes from Education Contributions prepared by the Branch Council, while a budget plan whose funding source comes from BOS funds ( School Operational Assistance) is prepared by the BOS Team in the Universities. 2. The largest use of BOS funds is in financing learning and extracurricular activities and financing subscriptions for power and or services. 3. Supervision and evaluation of financing at the Tamansiswa Pematangsiantar Branch is carried out in two ways depending on the type of use of funds. The use of funds sourced from students will be evaluated and checked by the Treasury Examiner Agency (BPP) and will make a report to the Branch Council. Meanwhile, the use of BOS funds from the government will be reported to the Head of Section (Principal), at the basic education level (SD and SMP) to the Pematangsiantar City Education Office, while for the secondary education level (SMA and SMK) it is reported to the North Sumatra Provincial Education Office through Realization Information System Application for Reports on the Use of BOS Funds (BOS SIRUP). 4. In supporting the learning process, the Tamansiswa Pematangsiantar Branch allocates funds for teachers in the preparation of learning tools and learning evaluations whose funding comes from the Government. Meanwhile, the funding for the implementation of learning is sourced from college funds (hourly tutoring honors according to the subjects taught) and BOS funds (for facilities and infrastructure as well as student needs). This form of research uses qualitative methods, namely methods that refer to research procedures that produce qualitative data, expressions or notes by researchers in observation activities. Qualitative research focuses more on the problems that exist at the time the research is carried out or actual problems and describes the facts about the problems investigated and their interpretations